2005
DOI: 10.1111/j.1445-2197.2005.03488.x
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐pseudopapillary tumours of the pancreas: 14 years experience

Abstract: Symptoms of SPTP are indistinct and preoperative diagnosis is often inaccurate. Magnetic resonance imaging improves SPTP diagnosis. In general, the prognosis of well-circumscribed SPTP is favourable after curative resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 17 publications
4
45
0
1
Order By: Relevance
“…1,16,18 Considering the favourable outcome, most current recommendations support aggressive management, targeting complete resection of both the primary tumour and the metastatic lesions whenever possible. 6,16,19 Pancreatic duct dilation was present in four of eight SPC patients in the present study. Furthermore, all four of these mass lesions, which were located in the pancreatic head, showed distal pancreatic ductal dilation.…”
Section: Discussionsupporting
confidence: 51%
“…1,16,18 Considering the favourable outcome, most current recommendations support aggressive management, targeting complete resection of both the primary tumour and the metastatic lesions whenever possible. 6,16,19 Pancreatic duct dilation was present in four of eight SPC patients in the present study. Furthermore, all four of these mass lesions, which were located in the pancreatic head, showed distal pancreatic ductal dilation.…”
Section: Discussionsupporting
confidence: 51%
“…This trend can be seen in our study, for example, 27 of 34 (79.4%) patients were diagnosed after the year 2000. Large single-institutional reports of SPN diagnoses after 2005 are summarized in table 4 [7,8,9,13,20,21,22,23,24,25,26,27,28,29,30,31,32]. …”
Section: Discussionmentioning
confidence: 99%
“…From the biological, molecular and oncological point of view, it represents and "enigmatic" tumor from which the origin, prognostic factors and natural history are unknown, having aroused a great interest and awareness in the last decades, when several clinical series and excellent reviews have been reported (4,(8)(9)(10)(11)13,(15)(16)(17)(22)(23)(24)(25)(26).…”
Section: Methodsmentioning
confidence: 99%